FFA4/GPR120 agonists: a survey of the recent patent literature. (November 2015) - Formicola, Rosa; Pevarello, Paolo; Kuhn, Christina; Liberati, Chiara; Piscitelli, Francesco; Sodano, Mariangela
FFA4/GPR120, a member of the rhodopsin family of G-protein-coupled receptors (GPCRs), is becoming an important target for therapeutic intervention in several areas of disease, including metabolic diseases, inflammation and cancer. In the last few years several patents on original chemotypes have been generated by different companies. In this review an analysis of the patents in the FFA4 agonism field is presented, with an emphasis on the documents published between 2013 and mid-2015. A discussion of the biological methods used in the patents is included. The general interest in this area is growing fast as half of the existing patents on FFA4 agonists have been issued after 2013. There is, however, a need of further diversifying new chemical classes away form the current substrate-like, carboxylic acid-containing agonists.